Ischemic Choroidal Diseases - Barth, Teresa; Helbig, Horst (Klinische Monatsblätter für Augenheilkunde, 2021)
Introduction Ischemic choroidal diseases are an underdiagnosed entity. The clinical pattern varies according to the size and the localisation of the affected vascular structure.Clinical Presentation In eyes with occlusion of the long posterior ciliary arteries, characteristic triangular patches of choroidal ischemia (Amalric sign) are seen, which in the course of time merge into well-defined areas of atrophy of the retinal pigment epithelium. Above the non-perfused choroidal areas, hyperpigmented, grouped lines appear (Siegrist streaks). Circumscribed ischemia of smaller choroidal arterioles and capillary vessels appears as multifocal, yellowish lesions in the posterior fundus (Elschnig spots). Vortex vein occlusion becomes manifest as exudative haemorrhagic choroidal swelling in the periphery.Causes of Choroidal Ischemia Apart from arterial hypertension as a major risk factor, some immunological disorders such as giant cell arteritis and systemic lupus erythematosus and haematological pathologies also affect choroidal perfusion. Furthermore, choroidal ischemia occurs due to local inflammation, as found in eyes with acute multifocal posterior placoid pigment epitheliopathy (APMPPE). Rarely, choroidal infarction is of iatrogenic origin or drug-induced. Recent advances in imaging, such as the introduction of enhanced depth imaging optical coherence tomography (EDI-OCT) and OCT angiography (OCT-A), have improved the visualisation of the choroidal vasculature and complement the classical angiographic procedures. In patients with age-related macular degeneration (AMD) and diabetes, some changes in choroidal blood flow and vascular structure have also been noted. While in AMD the choroidal pathologies correlate with the disease progression and the functional prognosis, the pathophysiological relationship between diabetic choroidopathy and retinopathy is currently unclear.Management and Conclusion With regard to the limited therapeutic options for choroidal ischemia, optimisation of the cardiovascular risk profile and the management of accompanying ocular and systemic diseases are essential.
Keywords: choroid; angiography; choroidal infarction; vascular occlusion; ischemia